Evaluasi Operasi PLTD Kamanggih Pasca-Interkoneksi pada Sistem Waingapu - Eri Prabowo; Trassanda Scudetto Widestomo Putra; Abdal Ghofar (JTM : JURNAL TEKNIK MESIN, 2026)
This study evaluates the operational effect of connecting PLTD Kamanggih to the Waingapu system through a 20 kV interconnection network. The study used operational, production, fuel, lubricant, cost, and system-capacity data from January 2023 to June 2024. The main indicators were Specific Fuel Consumption (SFC), Specific Lubricant Consumption (SLC), and Cost of Electricity Production (BPP). Before interconnection, PLTD Kamanggih had higher SFC, SLC, and BPP than PLTD Waingapu, namely 0.41661 liter/kWh, 0.00401 liter/kWh, and 5,785.48 Rp/kWh, while PLTD Waingapu recorded 0.27945 liter/kWh, 0.00012 liter/kWh, and 3,160.71 Rp/kWh. After the interconnection, Kamanggih's 0.114 MW load was supplied by the Waingapu system, which still had sufficient available capacity. The best comparison occurred between the second quarter of 2023 and the second quarter of 2024, where SFC decreased by 0.00729 liter/kWh or 2.59%, SLC decreased by 0.00012 liter/kWh or 73.94%, and BPP decreased by 87.57 Rp/kWh or 2.63%. The result indicates that 20 kV interconnection is effective as a dedieselization strategy to improve operational efficiency, reduce isolated diesel operation, and lower electricity production cost.